Negosiasi Maskulinitas dalam Keluarga Santri: Studi Kasus Pada Keluarga Santri Generasi Z di Yogyakarta - Hasan Daulah; Rr. Siti Kurnia Widiastuti (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study looks at how men in married generation Z Islamic boarding school families handle their roles as family leaders, considering the changes happening in society today. The study is driven by the change in how masculinity is seen, moving from a traditional view that focuses on male strength and control to a more connected and equal way of understanding manhood, influenced by religious beliefs and new ideas about gender. A descriptive case study was used, which involved detailed interviews with married Generation Z santri families in Yogyakarta. The data were looked at using Judith Butler's idea about how gender is performed to see how men's identities are made and shown in family life. The study shows that the way Generation Z santri express masculinity is a positive form of masculinity. It includes being responsible, communicating well, working together with others, and making decisions together with their spouses. Islamic boarding schools play an important role in helping families develop strong leadership by teaching important Islamic values, a sense of moral duty, and how to treat others with respect. Masculinity is worked out through talking and mutual understanding, which helps avoid conflict and creates more peaceful and fair family relationships. This research adds to the existing knowledge about masculinity, how genders relate to each other, and studies on Islamic families. It shows that for generation Z santri, being a man in an Islamic way isn't just following old, male-dominated traditions. Instead, it's a way of adapting and acting out being a man that mixes religious beliefs with today's ideas about gender. The results also offer practical recommendations for improving family education and promoting gender-responsive debate within Islamic boarding schools through the promotion of family leadership models that prioritize communication, mutual responsibility, and collaborative partnership